Frauds, deceptions, and swindles - Sifakis, Carl (Checkmark Books, 2001)
America has always had its share of shady characters, deceptive schemers, and get-rich-quick swindlers who leave victims penniless and duped. Here, over 80 entries examine America's most underhand plots - and the dishonest men and women who created and perpetrated them.